Deanna Bowen: God of Gods: A Canadian Play, Justina M. Barnicke Gallery, Hart House, University of Toronto - Suurtamm, Karen (Archivaria, 2020)
Deanna Bowen: God of Gods: A Canadian Play. Justina M. Barnicke Gallery, Hart House, University of Toronto. September 4 – November 30, 2019. Curated by Barbara Fischer with research by Maya Wilson-Sanchez.